Design and test of a gripper prototype for horticulture products. (April 2017) - Russo, Matteo; Ceccarelli, Marco; Corves, Burkhard; Hüsing, Mathias; Lorenz, Michael; Cafolla, Daniele; Carbone, Giuseppe
Abstract: This paper describes the design of a gripper for horticulture product grasping. The design solution has been achieved by means of a systematic approach by evaluating all the possible architecture. The proposed structure is optimized and numerically simulated. Then, a prototype has been built and tested in laboratory. The design process and test results are discussed to show the efficiency of the built prototype with lab tests.